Many : the diversity of life on Earth - Davies, Nicola, 1958- (Candlewick Press, 2017)
The more we study the world around us, the more living things we discover every day. The planet is full of millions of species of plants, birds, animals, and microbes, and every single one including us is part of a big, beautiful, complicated pattern. When humans interfere with parts of the pattern, by polluting the air and oceans, taking too much from the sea, and cutting down too many forests, animals and plants begin to disappear. What sort of world would it be if it went from having many types of living things to having just one?